Development finance cooperation amidst great power competition: what role for the World Bank?. (11th April 2023) - Morris, Scott
Abstract: The World Bank today faces parallel challenges to its operations and governance. The institution has since its founding provided financing on favourable terms to developing country governments to support national development efforts. Alongside these country demands, there are now calls for a new set of mandates and activities associated with global public goods. Advocates would have the Bank allocate large sums toward climate mitigation, pandemic response and preparedness, and other activities that may or may not align with national priorities in developing countries. The ability of the World Bank to strike an appropriate balance between country demands and global goods depends on the institution's shareholders. Yet, the deterioration in the bilateral relationship between the United States and China now threatens to undermine effective governance at the institution. This paper considers the challenge of competing demands on World Bank resources and the degree to which a resolution could depend on an agreement between the United States and China, one that sets the strategic direction of the institution and addresses the growing impasse on the question of China's shareholding in the Bank.